Metering of agricultural power supply in West Bengal, India: who gains and who loses? - Mukherji, Aditi; Das, B.; Majumdar, N.; Nayak, N.C.; Sethi, R.R.; Sharma, Bharat R.; Banerjee, Partha Sarathi (2008)
As a part of the ongoing power sectors reforms in India, the state of West Bengal is in the process of metering agricultural electricity supply. Based on primary data, this paper presents a first cut assessment of this initiative. Results suggest that the majority of the pump owners benefit from the reforms in two ways: first by having to pay a lower electricity bill for same usage and second through increased profit margins by selling water. This is because in response to changed incentive structure for water selling, water prices rose sharply by 30-50% immediately after metering. In contrast, water buyers have lost out by having to pay higher water charges and face adverse terms of contract. Impact of metering on operation of groundwater markets is less clear; they may expand, contract or remain unchanged. Same holds true for the volume of groundwater extracted, though water use efficiency may go up. At current tariff rates, the electricity utilities are likely to earn less revenue than before. There is also no evidence that quality of electricity supply has improved following metering. These findings are context specific and holds good for West Bengal where high flat tariff had fostered competitive groundwater markets and hence can not be generalised for other Indian states.